Women of quality : accepting and contesting ideals of femininity in England, 1690-1760 - Tague, Ingrid H., 1968- (Studies in early modern cultural, political and social history, 2002)
In the years following the Glorious Revolution, didactic writers and other social critics created a new discourse of 'natural' feminine behavior. This has been seen as the first stirrings of a middle-class ideology, opposed to the luxury and decadence of fashionable women, but using the correspondence and diaries of such aristocratic women, Tague traces the ways in which they adopted, adapted, and exploited these ideals of femininity to work to their own advantage.